Elevated Temperature Formability of Precipitation Hardenable Sheet Aluminum Alloys - DiCecco, Sante (University of Waterloo, 2025)
This thesis investigates the elevated temperature forming behavior of two age-hardenable aluminum alloys, AA6013 and a developmental 7000-series alloy (denoted AA7xxx), intended for automotive applications. Warm (150°C - 250°C) and hot (>=300°C) forming conditions were considered as well as a range of starting tempers to ascertain the potential benefits of elevated temperature forming. A major outcome of this work was the development and detailed documentation of a physically motivated method to assess formability, termed the Enhanced Curvature Method (ECM). The ECM utilizes stereoscopic digital image correlation (DIC) to detect the onset of necking based on changes in surface curvature. The ECM was validated at room temperature using AA5182-O sheet which exhibits a strong dynamic strain ageing effect that affects strain localization. The plane strain limit strains obtained using the ECM in Marciniak, Nakazima, and stretch-bend formability tests were consistent with two other formability characterization methods developed for room temperature, the ISO12004-2:2008 standard and the rate-dependent method developed by Volk and Hora (2011) termed the “linear best fit” (LBF) method. The average Marciniak plane strain limit strain for AA5182-O obtained using the ECM was 0.198, and in close agreement with the theoretical limit strain of 0.194 obtained from the instability model of Swift. The ECM was subsequently applied to characterize the room and elevated temperature formability of 2 mm thick AA6013 and AA7xxx. Both alloys were tested using a 76.2 mm wide dog-bone specimen geometry in a Nakazima-type test, that produced near plane-strain conditions. For AA6013-T6, when characterized using the ECM, warm forming did not offer a meaningful improvement in formability with increasing temperature over the tested ranges. The plane strain forming limit at both 230°C and room temperature (RT) was measured as approximately 0.18 with comparable scatter bands. To improve warm formability, AA6013 in a pre-aged (PA) temper was investigated. The PA temper was produced by solutionizing the material at 560°C for 10 minutes, water quenching, aging at 100°C for 4 hours then followed by a second water quench. The room temperature formability of the PA temper was significantly higher than that of the peak-aged temper with a major limit strain of 0.28. The elevated temperature formability of the PA temper, however, decreased relative to its room temperature formability. At 230°C, the major limit strain was reduced to 0.21 and attributed to aging occurring during the warm forming process. A significant outcome of the AA6013 work was the observation that a relatively short secondary aging cycle (less than 410 s) at 235°C after forming, combined with a pre-aged initial temper, could result in a stress-strain response similar to the baseline T6 temper, regardless of a subsequent paint-bake. This processing route offers a potential pathway to achieve T6 strength levels with a greater than 50% improvement in formability when comparing the RT PA limit strain of 0.28 to the baseline T6 limit strain of 0.18. The effect of initial temper on the warm formability and aging response of AA7xxx was also investigated for three tempers: pre-aged (PA), peak-aged (T6), and over-aged (T76), all tested using a 76.2 mm dog-bone specimen. The PA temper exhibited the highest formability at room temperature, with a major true limit strain of 0.21. At 150°C, the limit strain for the PA temper increased to 0.24, representing a modest improvement. At higher temperatures (175°C and 200°C), the results were not as clear, with measured dome heights decreasing and strains relatively unchanged. Similar to the AA6013 PA temper, the formability gains at elevated temperature for the AA7xxx PA temper were modest. Warm forming at 200°C, followed by a paint-bake, resulted in both the PA and T6 tempers achieving ductility and strength levels similar to those of the as-received T76 temper. The hot-stamping and die quenching (DQ) process was investigated as an alternative means to enhance the formability of AA7xxx. The DQ process resulted in a major limit strain of 0.76 in plane strain. Under an interrupted, isothermal (300°C) hot-stamping operation, a major limit strain of 0.53 in plane strain was observed. Both limit strains were significantly higher than the room temperature formability of 0.12 measured for the as-received T76 temper and that achieved using warm forming. Surface defects, however, such as orange peel, were observed for major strain levels in excess of approximately 0.45. A major conclusion of this work is that while both AA6013 and AA7xxx alloys demonstrated only modest improvements in formability when warm formed in their as-received conditions, a better balance of strength and formability can be achieved by leveraging pre-aged starting tempers combined with post-stamping aging cycles. The die quenching process results clearly show that excellent formability of AA7xxx series alloys can be achieved with additional process complexity. The ECM, a key outcome of this work, offers an effective and robust method for quantifying formability at both room and elevated temperatures. Future work should explore faster warm forming processes to overcome the rapid aging effects observed in the PA tempers. Additionally, other aluminum alloys should be evaluated for warm forming and die quenching to identify alloys that may offer a greater positive response to elevated temperature forming.
Keywords: aluminum; formability; digital image correlation; aging kinetics; warm forming; die quenching; curvature; nakazima; marciniak; AA5182-O; AA6013; AA7xxx